Reinventando horizontes: uma análise sócio antropológica do processo de proposição do projeto de vida de jovens negras de Santa Maria/RS - Arispe, Fernanda Nunes da Silva (2016)
This work has as theme the life project of black youth collective members named Youth Black Women Santa Maria. In order to investigate what and how to articulate some aspects of the lives of these young people taken into account in the construction of their projects, we seek to understand how their belonging to social class, racial and gender operate together in this process. Therefore, methodologically mobilized authors such as Geertz, Cardoso de Oliveira and Da Matta. In conceptual discussion, highlight Gilberto Velho and its design project; Dumont and his studies of individualismo; Bourdieu and the fusion of individuality and externality; and Kimberle Crenshaw and Sueli Carneiro in his discussion about the depressive triad social stratum-gender-race. We note, therefore, that the projects of the collective members observed are strictly crossed by issues of social class in which they operate their families, the structure and organization of the same, as well as the affirmation of their identity as black women and the implementation of public policies for the black population.